Short-duration chickpea (Cicer arietinum) for vegetable purpose - SANDHU, J S; SEKHON, H S; SINGH, GURIQBAL; BAINS, T S; GUPTA, S K; KAUR, AJINDER; SAXENA, A K; SHARMA, S (The Indian Journal of Agricultural Sciences, 2011)
Field experiments were conducted during 2000-2003 to the evaluate sowing time and spacing to maximize the green seed yield of ’ICCV 96029’ and ’ICCV 96030’ chickpea(Cicer arietinum L.). In the field experiments ’ICCV 96029’ and ’ICCV 96030’ along with check variety ’PBG 1’ were sown on 21 September, 1 October and 10 October during 2000-2003. Green grain and biomass yields were recorded after 75 days of sowing. In the years 2001 to 2003, an additional spacing of 20 cm was also added. The genotypes ’ICCV 96029’ and ’ICCV 96030’ were early in flowering and poding than the ’PBG 1’. After 75 days ’ICCV 96029’ gave the highest mean green grain yield of 2 062 kg/ha in 1 October sown while ’ICCV 96030’ gave the highest mean green grain yield of 1 888 kg/ha in the 10 October sown crop. The check variety ’PBG 1 ’ did not bear the poding in 75 days. Narrow spacing of 20 cm gave significantly more green grain yield than 30 cm spacing. In general short-duration genotypes gave more than 5 000 kg/ha biomass in 75 days irrespective of genotype or sowing date. Both the genotypes possessed comparable good quality traits